The book of Psalms - Declaissé-Walford, Nancy L.; Jacobson, Rolf A. 1965-; Tanner, Beth LaNeel (William B. Eerdmans Publishing Company, 2014)
Reflecting the combined insights and strengths of three superior biblical scholars, this book is the most complete and detailed one-volume commentary available on the Psalms. Nancy deClaisse-Walford, Rolf Jacobson, and Beth LaNeel Tanner offer a succinct introduction to the Psalter, a new translation of all the psalms that takes special account of the Dead Sea Scrolls, and individual entries on each psalm unit. Throughout their commentary they drew on state-of-the-art research on the canonical shape and shaping of the Psalter and give nuanced attention to the poetic nature of the psalms
Includes bibliographical references (pages 47-51) and indexes
Keywords: Bibel -- Psalmen; Bible / Psalms / Commentaries; Bibel; Kommentar